2018
DOI: 10.1016/j.humov.2018.03.004
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the effects of mental and muscular fatigue in soccer players’ performance

Abstract: This study examined the effects of induced mental and muscular fatigue on soccer players' physical activity profile and collective behavior during small-sided games (SSG). Ten youth soccer players performed a 5vs5 SSG under three conditions: a) control, playing without any previous activity; b) muscular fatigue, playing after performing a repeated change-of-direction task; c) mental fatigue, playing after completing a 30 min Stroop color-word task. Players' positional data was used to compute time-motion and t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
118
3
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 119 publications
(122 citation statements)
references
References 48 publications
(104 reference statements)
0
118
3
1
Order By: Relevance
“…In other two studies, no clear effects of mental fatigue were identified in small-sided games. 42,44 Coutinho et al 41 observed shorter total distances covered and Kunrath et al 43 found higher values of distance covered at speeds between 10 and 12.9 km/h and ≥ 18 km/h.…”
Section: Physical and Physiological Performancementioning
confidence: 99%
See 3 more Smart Citations
“…In other two studies, no clear effects of mental fatigue were identified in small-sided games. 42,44 Coutinho et al 41 observed shorter total distances covered and Kunrath et al 43 found higher values of distance covered at speeds between 10 and 12.9 km/h and ≥ 18 km/h.…”
Section: Physical and Physiological Performancementioning
confidence: 99%
“…Four different cognitive tasks were used as a protocol for inducing mental fatigue, the AX-CPT (90 minutes), the Stroop paper [38][39][40][41] and computer version (20 -30 minutes) 42,43 , and the motor coordination task 44 . In control condition, the subjects read magazines [38][39][40] , watched TV documentaries 30,42 , and performed a warm-up lasting the same time as the intervention condition 44 .…”
Section: Cognitive Tasksmentioning
confidence: 99%
See 2 more Smart Citations
“…Coutinho et al (2017) similarly showed that after game-based and sports specific cognitive fatigue-inducing tasks players spent less time synchronized in the lateral direction and reduced their speed of team dispersion and contraction during the SSG. A follow up study by Coutinho et al (2018) improved on the design of the previous study (counterbalancing the fatigue condition between teams), and showed that after cognitive fatigue, there was a greater distance between dyads and a reduction in the teams' stretch index and time spent longitudinally synchronized as measured by GPS. Together, the results demonstrated that whilst cognitively fatigued, a player's ability to recognize important environmental cues and to properly monitor and adjust the performance in a timely manner becomes impaired.…”
Section: Physical Tasks That Emphasize Perception and Cognitionmentioning
confidence: 99%